The Isolation and Replication of African Swine Fever Virus in Primary Renal-Derived Swine Macrophages - Oh, Taehwan; Do, Duy Tien; Vo, Hung Van; Kwon, Hyeok-il; Lee, Seung-Chul; Kim, Min Ho; Nguyen, Dung Thi Thu; Le, Quang Tin Vinh; Tran, Tan Minh; Nguyen, Toan Tat; Lee, Joo Young; Chae, Chanhee (Frontiers in Veterinary Science, 2021)
African swine fever virus (ASFV) causes hemorrhagic disease in domestic pigs by replicating mainly in monocyte/macrophage lineages. Various primary cells including pulmonary alveolar macrophages have been used for the propagation of ASFV on this account. However, ethical constraints and consistency problems exist as it is necessary to harvest same phenotype of primary cells in order to continue a study. We suggested renal-derived swine macrophages as a novel primary cell candidate to address these issues. These primary cells proved to be permissive to both cell adapted ASFV and a wild-type ASFV. Compared to the commercial cell line MA-104, the renal-derived macrophages were more suitable to isolate the field virus. The consistent molecular characteristics of the renal-derived macrophages were demonstrated by immunocytochemistry with antibodies against macrophage cell surface markers including CD163, CD172a, and Iba-1. Viral protein p30 and p72 expression in ASFV infected macrophages was confirmed by immunocytochemistry by use of specific monoclonal antibodies. We observed increase of cell-free viral DNA and infectious virus titer in infected cell supernatant in successive days-post-infection. These results demonstrated that primary renal-derived swine macrophages are useful for ASFV isolation and propagation in terms of cell phenotypes, susceptibility to the virus, and virus production.